Analisis Perbandingan Gadai Syariah dan Gadai Konvensional di Tinjau Hukum dan Prinsip - Putra, Dewa Pratama; Wati , Asiah (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2023)
Pawn is a right acquired by an individual who owes a movable property, which is handed over to them by a debtor or a representative, granting the debtor the authority to receive payment for the goods in advance compared to other debtors, excluding auction costs and salvage expenses. Sharia pawning (known as Rahn) involves using one of the borrower's assets as collateral for the loan they receive. This study seeks to establish a comparison between conventional pawning and sharia pawning (rahn). The research aims to provide insights and understanding to all relevant parties regarding the comparative aspects of conventional pawning and sharia pawning (rahn). The research methodology employed is library research, utilizing data collection techniques such as gathering books, journals, and previous works related to conventional pawning and sharia pawning (rahn). The researcher employs qualitative data analysis for data interpretation. Based on the described research, it can be concluded that both conventional pawns and sharia pawns share similarities in that they are prohibited from exploiting the pawned goods, and the pawnee has the right to sell or auction the pawned goods once the loan period expires. The distinction between conventional pawning and sharia pawning lies in the legal foundation. Conventional pawning relies on the Criminal Code, while sharia pawning is guided by the DSN MUI Fatwa on Rahn. In conventional pawning, the contract involves a single debt agreement with a movable goods guarantee from a conventional legal perspective. The Ministry of SOEs oversees conventional pawning, while the Sharia Supervisory Agency (BPS) and the Financial Services Authority (OJK) oversee sharia pawning. Conventional pawns involve interest charges, whereas sharia pawns incur maintenance costs. In conventional pawning, pawned goods can be auctioned, while in sharia pawning, they can be sold.